The Fiscal Federalism: the Main Instrument of Good Economic Governance - Alina Ligia Dumitrescu (Revista de Economie Mondială, 2014)
The article analyzes the need, role and principles underlying good governance in the European Union, namely: openness, participation, accountability, effectiveness and cohesion. Subsequently, the research continues with the definition of the fiscal federalism concept, focusing on the benefits of the “economics of multi-level governance”. Fiscal federalism is presented as a main instrument of good economic governance that can bring benefits in terms of fiscal consolidation, the efficient use of public funds and the efficient allocation of functions between different levels of authority within the multi-level governance.